2016
DOI: 10.3109/09273948.2016.1160128
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenges in Inflammatory Choroidal Neovascular Membranes

Abstract: A high index of suspicion and comparison of serial fundus photographs to identify the earliest clues of inflammatory CNVMs are important to prevent diagnostic delays and poorer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…A diverse array of pathological processes involving the retinal pigment epithelium (RPE) and Bruch’s membrane may lead to the formation of CNV. Age-related macular degeneration (AMD) and myopia are the conditions that most commonly lead to the development of CNV, with ocular inflammation being the next most frequently implicated [ 1 3 ]. CNV may occur in a wide range of uveitides including both infectious and non-infectious etiologies.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A diverse array of pathological processes involving the retinal pigment epithelium (RPE) and Bruch’s membrane may lead to the formation of CNV. Age-related macular degeneration (AMD) and myopia are the conditions that most commonly lead to the development of CNV, with ocular inflammation being the next most frequently implicated [ 1 3 ]. CNV may occur in a wide range of uveitides including both infectious and non-infectious etiologies.…”
Section: Reviewmentioning
confidence: 99%
“…Active uveitic chorioretinal lesions show early isofluorescence (but mostly hypofluorescent) with late leakage . On the other hand, inactive atrophic lesions show early hypo-/isofluorescence with late staining (indicating RPE window defect) without any leakage [ 1 3 ]. Thus, there are very subtle differences in the appearance of FA between CNV lesions and active/inactive retinochoroidal inflammatory lesions.…”
Section: Reviewmentioning
confidence: 99%
“…Reportedly, the common types of uveitis that cause CNV are thought to include punctate inner choroidopathy, multifocal choroiditis, and VKH [13]. CNV complicating uveitis is often difficult to diagnose due to poor mydriasis, vitreous opacity, and cystoid macular edema, etc., and therefore, treatment is highly likely to be delayed [14]. For the diagnosis, indocyanine green angiography, in addition to OCT and fluorescein angiography, is useful [15].…”
Section: Discussionmentioning
confidence: 99%
“…As for fundus features, in addition to multiple choroidal scar lesions, macular scars, scars around the optic disc, and subretinal fluid, a subretinal hemorrhage may lead to the detection of the CNV. Although subretinal hemorrhage due to a rupture of the CNV seems relatively rare, Bansal et al [14], who examined 73 eyes of 60 patients with uveitis complicated by CNV, reported that subretinal hemorrhage was detected in 5 eyes. However, and as far as we know, there have been no previously reported cases in which pneumatic displacement with gas tamponade was performed for submacular hematoma, as in our present case.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in another retrospective study involving 6850 uveitis patients, 73 eyes of 60 patients (0.87%) were found to have inflammatory CNV. 11  Of these 73 eyes, 52% (38 eyes of 29 patients) had CNV at the first presentation and the remaining 48% (35 eyes of 31 patients) developed CNV during the course of follow-up. Only 1 patient with CNV had a diagnosis of SO.…”
Section: Introductionmentioning
confidence: 97%